Precautionary behavior toward dengue virus through public service advertisement: Mediation of the individual’s attention,iInformation surveillance, and elaboration - Raza, Syed Hassan; Iftikhar, Moneeba; Mohamad, Bahtiar; Pembecioğlu, Nilüfer; Altaf, Mohsin (Sage Journal, 2020)
The study examines the role of a health-related promotional campaign launched in Pakistan in the context of advertising campaign to improve precautionary behavior toward dengue virus (PBDV). The focus of this study is to investigate the mediation of individual’s attention, information surveillance, elaboration, and also the moderation of demographic features (e.g., gender, educational level, and dengue affected survival) in the relationship between the exposure of dengue-related public service announcements (DPSA) and PBDV. Telephonic interview technique was used to establish a representative sample (N = 1,251) from Punjab (dengue-affected province of Pakistan) using a computer-assisted telephone survey software. The outcomes clarify the application of cognitive mediation model in the context of health communication. The findings revealed that individual’s attention and information surveillance have considerable mediating effects on PBDV and DPSA relationship. Surprisingly, however, there is no indirect effect of elaboration on PBDV. The findings provide practical recommendations to public organizations while designing health communication strategies.